Arrangement of SLUMS in Tapak Kuda Village, Langkat Regency - Yoki Eka Prianto; Abdi Sugiarto; Cut Nuraini (CV. Doki Course and Training, 2026)
This study aims to analyze the existing conditions of slums in Tapak Kada Village, Langkat Regency, evaluate the factors that cause the existence of slums even though there has been a government improvement program, and formulate a sustainable restructuring strategy. The research uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observations, and documentation studies, and analyzed using reduction, presentation, and conclusion drawn. The results of the study show that the condition of the slums in Tapak Kuda Village still faces significant problems in terms of settlements, sanitation, and infrastructure, including uninhabitable houses, poor sanitation, limited drainage, and inadequate environmental roads. Factors that cause the existence of slums include the economic limitations of the community, settlement density, low citizen participation, environmental challenges due to land conversion, and limited coordination and government resources. The proposed restructuring strategies include the physical improvement of settlements, participatory approaches, socio-economic empowerment, integration of environmental aspects, and multi-stakeholder collaboration. The role of the government and the active participation of the community have proven to be the key to the success of sustainable slum planning. This research is expected to provide input for the government and related stakeholders in designing a slum management program that is more effective, sustainable, and improves the quality of life of the people of Tapak Kuda Village.